The new home : a handbook for tenants (London : The Health and Cleanliness Council, 1937)
1937 1937 1930s 24 pages : illustrations THE BATHROOM AND CLOSET TOILET ARTICLES ARE STRICTLY PERSONAL All members of the family should have their own toilet articles, and no tooth-brush or hair-brush should be used except by its owner. Wash cloths and face towels can be home-made at little cost — the best parts of worn-out sheets and other articles can be made into face cloths and towels. Wash all toilet brushes regularly in a good soapy lather and dry in the sun if possible. [illustration] Keep your brushes clean. WASH ALL OVER EVERY DAY A daily bath is desirable and with a little planning can usually be managed. Remember to rinse out the bath for the next person. KEEP THE BATHROOM CLEAN Both bathroom and water-closet should be kept clear of unnecessary articles. If you have a small wall-cupboard in the bathroom for first-aid necessities, medicine glass etc., see that both the cupboard and contents are always spotlessly clean. Do not allow unwanted medicines to accumulate. Make sure that no poisonous substances are stored in the medicine cupboard. [illustration] Useful medicine cupboard. THE USE OF THE WATER-CLOSET When the children are old enough to use the water-closet, teach them to use it with cleanliness, and to leave it clean. Teach them always to wash their hands immediately after using the water-closet. Toilet paper is not expensive. The most frequent cause of blocked drains — a menace to health — is the use of newspaper. 13 177/5/8/2